Highly Efficient and One-pot New Betti Bases: PEG-400 and Al2O3 Mediated Synthesis, Optimizations, and Cytotoxic Studies - Piludiya, Reshmabanu; Kapadiya, Khushal M. (Letters in Drug Design & Discovery, 2024)
BackgroundMulticomponent reactions (MCRs) have proven as one of the best alternatives to minimize several environmental consequences, mainly the use of hazardous chemicals, by-products, and severe production processes. Literature reveals that MCRs with PEG-400 and metal oxide-based greener media provide a new and useful strategy for the construction of biologically potent organic systems.ObjectiveThe present study aimed to synthesize newer Betti bases by a modified Betti reaction employing a highly efficient catalyst for the direct synthesis of a novel class of non-racemic amino benzyl naphthol ligands under green solvent media. The involvement of the articulated framework (4a-4j) was studied against nine cancer panels (NCI-60 cell lines) in terms of inhibiting/killing cancer cells.MethodsFor the modification of the Betti reaction, we used 2-aminopyridin-3-ol, aromatic aldehydes, and a naphthol system using greener media employing PEG-400 and alumina as a prime active and highly selective catalyst. Furthermore, the antiproliferative activity against NCI-60 human cancer cell lines (GI50) was used for the development of pharmacologically active compounds and exhibited the single dose (10-5 M) study.ResultsBased on greener media synthesis, recompenses of ease of workup, less reaction time, higher yield, and higher atom economy, as well as environmentally friendly, were reported. Betti bases were obtained at a yield of 87-98% and characterized by spectroscopic techniques. Among the synthesized scaffolds, compound 4b was found to be extra potent in melanoma cancer [MDA-MB-435], while compound 4h showed promising inhibition in leukemic cancer cell lines [HL-60(TB) and MOLT-4].ConclusionA straightforward way for an efficient synthesis of Betti bases was developed via the reaction of naphthol and aldehydes with amines in PEG-400 media. An Al2O3 was effectively catalyzed in the Betti reaction in excellent yields without the formation of any other by-product in atom economy and environmentally benign way. The newly synthesized hybrids were tested in vitro against a panel of cancer cell lines, and some of the compounds exhibited significant inhibitory anti-proliferative effects. The most potent compounds (4b and 4h) showed interesting results, and compound 4b was found extra potent in melanoma cancer cell lines with -62% GI values.
Keywords: PEG-400